PEMANFAATAN TEPUNG KOMPOSIT PISANG GOROHO (Musa acuminate) DAN UBI JALAR KUNING (Ipomoea batatas. L) SEBAGAI BAHAN BAKU PEMBUATAN CRUST PIE - Ria, Nizar; Rawung, Dekie; Nurali, Erny J. N. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2019)
AbstractThe objectives of this study were to analyze the composition and sensory quality of the crust pie made of composite flour of goroho and yellow sweet potato. This study was conducted in a completely randomized design with 4 different composition ratio of goroho plantain flour to yellow sweet potato flour, i.e., A (80% : 20%), B (70%: 30%), C (60%: 40%), and D (50% : 50%). The results of the study showed that the chemical composition of pie crust were in a range of 2.87% - 4.74% for moisture content, 2.66% - 2.72% for ash content, 32.10% - 32.95% for fat content, 5.90% - 6.06% for protein content, 3.76% - 4.77% for crude fiber, and 50.04% - 55.50% for carbohydrates content. The pie crust made from composite flour 50% goroho : 50% yellow sweet potato was the most preferred by panelists in terms of color, aroma, taste and texture with a value of 3.89 (like).Keywords: pie crust, composite flour, goroho plantain, sweet potato